Risk profile of inorganic arsenic in Nile Tilapia (Oreochromis niloticus) consumed in the Philippines - Viquezo, Katharina Nilda Ann T.
Dietary exposure to inorganic arsenic (As-in) occurs through contaminated water and food, such as Nile tilapia (Oreochromis niloticus), causing multiple adverse health effects such as skin, lung, bladder, and liver cancers. This study conducted a food safety risk profiling of inorganic arsenic in tilapia by [1] determination of the data gaps in the risk profiling of arsenic in tilapia by the Filipino consuming population; [2] identification and characterization of As-in as a food hazard; [3] estimation of dietary exposure (DE) and risks based on uncertainties, variabilities, and assumptions; and [4] determination of available risk management options for arsenic in tilapia. Gaps identified in the Philippines included: dose response models, disaggregated consumption data, reports of illnesses and poisoning, absence of maximum levels, local monitoring data on As-in in tilapia. Dietary exposures (in mg/kg bw/wk) to As-in in the consumption of tilapia for male and female were calculated using consumption data from DOST-FNRI (2022) and levels of As-in obtained from PRPP (2022). As-in levels in Nile tilapia were all below the 0.015 mg/kg provisional tolerable weekly intake (PTWI) previously established in the 33rd meeting of the Joint Expert Committee for Food Additives (JECFA) (TRS 776-JECFA 33/27). Mean DE ranged from 0.00029 mg/kg bw/wk to 0.00041 mg/kg bw/wk for males and 0.00031 mg/kg bw/wk to 0.00043 mg/kg bw/wk for females across all age groups, with infants and preschool children having the highest levels. For the high (97.5th) consuming population, DE ranged from 0.00030 µg/kg bw/wk to 0.00047 mg/kg bw/wk for males and 0.00033 mg/kg bw/wk to 0.00047 mg/kg bw/wk for females, where infants and preschool children similarly recorded high levels. It can be concluded that tilapia is safe for consumption and has low levels of As-in since the DE values are lower than the PTWI for As-in. There are currently no available maximum levels of arsenic in tilapia, both internationally and in the Philippines.